The Implicit Meanings of Negative Confession Article Headings in the New Weekly - SEPTYLILA WIBOWO, ERIZA (Language Horizon: Journal of Language Studies, 2013)
Abstract Some articles of the magazines usually contain implicit meaning. The implicit meaning can attract to the reader to read and to buy. This study tries to explain how the narrator uses implicit meaning and what the purpose of the narrator uses it in the New Weekly magazine. This study uses some theories, such as Yule, Levinson, and others. The theory used in this study is pragmatics, because it involves reference, co-text, and presupposition. The research design of this study is descriptive qualitative. The data used came from the nine articles in the New Weekly magazine. All of the data in this study were created by nine headings in the New Weekly magazine. Then, this study aims to know how and what the purposes of the narrator uses the implicit meaning. In conclusion, this study finds that the narrator uses reference, co-text, and presupposition to explain and analyze the implicit meaning in the heading of magazine. Then, the narrator’s purpose is to tease the nine famous artists. Key terms: implicit meaning, reference, co-text, presupposition